Evaluation of groundwater-caused deformation patterns in a metropolitan area using time series InSAR and retrieval of vertical and east-west displacement: a case study in Taipei City - Ajay Saraswat; Ya-Lun S. Tsai; Jen-Yu Han (Geomatics, Natural Hazards & Risk)
This study explores the influences of groundwater fluctuations in an urban area which lead to long-term ground surface subsidence using a time-series synthetic aperture radar interferometry (InSAR) technique. Unlike most prior studies that only focus on line-of-sight (LOS) deformation, assume negligible horizontal movements, and quantify InSAR-groundwater relationship on a sparse temporal scale, this study utilized the Persistent Scatterers InSAR (PS-InSAR) technique to extract east-west and vertical displacement by decomposing Sentinel-1 ascending and descending datasets spanning from 2018 to 2022. Additionally, an approach was proposed to effectively quantify the relationship between changes in groundwater levels and vertical displacement on a daily basis. The results underwent robust validation against ground-based leveling surveys, revealing a satisfactory NRMSE of 1.06 mm/yr. Furthermore, founded on the estimated vertical displacement, three districts within Taipei City (e.g. Wugu, Xinzhuang, and Taishan) were identified as subsidence hotspots, with maximum vertical deformation rates reaching −11.77 mm/yr. Eventually, the correlation analysis and quantification between vertical displacement and daily groundwater data underscore long-term groundwater fluctuations as the primary cause of subsidence. These findings, derived from InSAR-based 2D displacements, have proven valuable in understanding groundwater-caused ground subsidence hazards in urban areas and empowering relevant stakeholders to set out corresponding adaptation and mitigation measures.